Kadar Asam Urat Pasien Diabetes Melitus Tipe 2 - Linda Ramadhanti; Devi Etivia Purlinda (Poltekkes Kemenkes Semarang, 2021)
Patients with type 2 diabetes mellitus are about 90% of all cases of DM in the world. Type 2 diabetes is caused by the body's inability to respond properly to insulin or is called insulin resistance. Insulin resistance causes hyperglycemia and hyperinsulinemia which results in decreased function of uric acid excretion in the kidney tubules, and causes an increase in uric acid in the blood or hyperuricemia. This type of research is descriptive, with a cross sectional approach in May for 5 days from May 17 to May 21 2019. The research sample is type 2 DM outpatients, at Dr. Hospital. Adhyatma MPH consisted of 24 people who were taken based on total sampling who agreed to the informed consent, were over 20 years old, had no history of gout, and fasted for 10-12 hours. The purpose of this study was to determine the uric acid levels of type 2 DM outpatients based on gender, age, and blood pressure at Dr. Hospital. Adhyatma MPH. The results showed that normal uric acid levels in type 2 DM outpatients were 14 people (58.3%) and hyperuricemia 10 people (41.6%). 7 patients (29%) each had normal urate levels. The highest normal uric acid levels were in patients aged over 55 years as many as 9 people (37.5%) and 10 people with hypertension (41.7%). The most hyperuricemia occurred in 6 female patients (25%), 6 patients over 55 years old (25%) and 6 patients with hypertension (25%).